A Prospective Randomized Controlled Trial Comparing Physical Therapy With Independent Home Stretching for Plantar Fasciitis. Issue 14 (15th July 2022) - Kaiser, Philip B.; Keyser, Cornelia; Crawford, Alexander M.; Bluman, Eric M.; Smith, Jeremy T.; Chiodo, Christopher P.
Abstract : Background: Although formal physical therapy (PT) is effective in treating plantar fasciitis (PF), it is unclear how this compares with home-based plantar fascia stretching (HS). Methods: Fifty-seven patients with PF were enrolled in a prospective randomized trial comparing PT with HS. Visual analog scale (VAS), Foot and Ankle Ability Measure (FAAM), and Short Form (36) Health Survey (SF-36) scores were analyzed at 6 weeks, 3 months, 6 months, and 1 year. Results: At 6 months, VAS improved in both HS (35% decrease; P < 0.001) and PT (26% decrease; P = 0.002) relative to baseline. FAAM Activities of Daily Living scores improved 13.0% ( P = 0.005) in HS and 21.3% ( P < 0.001) in PT at 6 months relative to baseline. The SF-36 Physical Component Summary Scores demonstrated improvement at all time points in both groups. There were no notable intergroup differences in VAS, FAAM, or SF-36 at any time point. Dicussion: The clinical outcomes of a home stretching protocol and PT did not markedly differ for the treatment of PF. Level of Evidence: Therapeutic Level I.